The Immune Landscape and Prognostic Immune Key Genes Potentially Involved in Modulating Synaptic Functions in Prostate Cancer - Zhu, Sha; Han, Xu; Qiao, Xianli; Chen, Shengxian (Frontiers in Oncology, 2020)
Background: Increasing evidence has indicated an association between differentially expressed genes (DEGs) in tumor infiltrating immune cells and clinical outcome. The aim of this research is to investigate the influence of tumor microenvironment on gene expression profile of tumor infiltrating immune cells (TIICs) and to identify their potential markers for modulating immune cell function in prostate cancer. Methods: In our research, CIBERSORT algorithm was utilized to calculate the proportion of the TIICs in 164 tumor and 18 control samples from the TCGA cohort. The differential expression analysis was conducted using R, and then the functional and pathway enrichment of the DEGs were analyzed using Database for Annotation, Visualization and Integrated Discovery database, followed by integrated regulatory network analysis. Results: As a result, nTreg, B cells, Th1 and DC cells were significantly increased, accompanied by largely decreased of NK and NKT cells. Expressed immune-related gene correlation analysis showed that the signature gene expression extent of CD8 T cells were positively associated with CD4 memory activated T cells, but negatively correlated with that of CD4 memory resting T cells. In addition, a total of 128 differentially expressed genes were identified. CytoHubba analysis obtained six hub genes, of which three prognostic-associated potential key molecules including CAV1, FLNA, and VCL were mainly involved in biological processes associated with regulation of organic substance and synaptic connections. Conclusions: This study provides a comprehensive understanding of the landscape of TIICs and roles of the hub genes which may be valuable markers in PCa diagnosis and immunotherapy.